PRODUKSI BIODIESEL DARI MINYAK JELANTAH MENGGUNAKAN KATALIS KALSIUM OKSIDA - Yulia Tri Rahkadima; Putri Abdi (Journal of Research and Technology, 2016)
The transesterification reaction has performed to convert waste cooking oils into biodiesel with assistant of heterogen catalyst of calcium oxide using reactor in a laboratory . The reaction was performed in two stages that is the esterification followed transesterification reaction. The aim of research is to study the effect of temperature and time reaction on viscosity and biodiesel yield. The results showed that obtained biodiesel had viscosity value in accordance with SNI 04-7182-2006 about diesel-fuel viscosity. At lower temperature (40, 45, and 50oC), the longer reaction time could lead to the increasing of biodiesel yield. Meanwhile, at higher temperature reaction (55oC and 60oC) the longer reaction time could reduce biodiesel yield. The highest biodiesel yield was obtained at following reaction condition: temperature reaction 50oC, 6 hours reaction time, ratio oil:MeOH= 1:48 molar ratio, % wt CaO = 8% to weight of waste cooking oil.